E-government development and diffusion inhibitors and facilitators of digital democracy - Sahu, Ganesh P.; Dwivedi, Yogesh Kumar; Weerakkody, Vishanth; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book provides a comprehensive, integrative, and global assessment of the e-government evolution in terms of real-life success and failure cases"--Provided by publisher.
Framework for e-government portal development -- E-government interoperability -- An explorative study of dynamic influences on ICT-led developmental impact at community level -- Tracking the digital divide -- Making ICT more meaningful for governance in rural areas -- Impact of e-government implementation on poverty reduction in rural India -- E-governance -- Application of natural language processing (NLP) techniques in e-governance -- Assessing e-governance online-service quality (EGOSQ) -- The success model of evolution from government to e-governance -- Technology acceptance of free wireless internet park initiatives -- A bibliometric analysis of electronic government research -- Towards an e-governance grid for India (E-GGI) -- E-Halli -- E-government implementation in Oman -- Telecentres.
Includes bibliographical references (p. 299-324) and index.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on Aug. 31, 2010).
Keywords: Internet in public administration; Information technology -- Government policy; Internet in public administration -- India; Information technology -- Government policy -- India; Digital democracy; E-government development; E-government diffusion; E-government interoperability; E-government portal development; Electronic government research; Global digital divide; Government to e-governance; Natural language processing; Wireless Internet initiatives; Electronic books